2007
DOI: 10.1162/jocn.2007.19.4.671
|View full text |Cite
|
Sign up to set email alerts
|

Social Mind Representation: Where Does It Fail in Frontotemporal Dementia?

Abstract: We aimed at investigating social disability and its cerebral correlates in frontotemporal dementia (FTD). To do so, we contrasted answers of patients with early-stage FTD and of their relatives on personality trait judgment and on behavior prediction in social and emotional situations. Such contrasts were compared to control contrasts calculated with answers of matched controls tested with their relatives. In addition, brain metabolism was measured in patients with positron emission tomography and the [(18)F]f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 65 publications
8
69
0
3
Order By: Relevance
“…Poor metacognitive awareness has been directly related to impaired empathy (O'Keeffe et al, 2007). It was also proposed that impaired awareness for social deficits results from impaired updating of autobiographical information, stored as semantic knowledge about the self, located in the temporal lobes (Ruby et al, 2007). Indeed, failure to update self-relevant knowledge due to memory deficits is a proposed mechanism for impaired self-awareness in patients with Alzheimer's disease as well (Mograbi et al, 2009).…”
Section: Clinical Relevance To Neurodegenerative Diseasesmentioning
confidence: 99%
“…Poor metacognitive awareness has been directly related to impaired empathy (O'Keeffe et al, 2007). It was also proposed that impaired awareness for social deficits results from impaired updating of autobiographical information, stored as semantic knowledge about the self, located in the temporal lobes (Ruby et al, 2007). Indeed, failure to update self-relevant knowledge due to memory deficits is a proposed mechanism for impaired self-awareness in patients with Alzheimer's disease as well (Mograbi et al, 2009).…”
Section: Clinical Relevance To Neurodegenerative Diseasesmentioning
confidence: 99%
“…In general, the inability to recognize neurological symptoms has been termed as 'loss of insight' [1,2] or 'anosognosia' [3,4] , a term originally used for unawareness of hemiplegia but now adopted to denote the lack of recognition of any disease-specific acquired symptom. Anosognosia for cognitive and behavioral impairment occurring in dementia is clinically relevant and has important consequences on compliance with treatment and caregiver burden [5] .…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical and neuroradiological studies [17,18,19,20] have revealed that anosognosia is associated with impairments of the right frontal lobe and frontal executive function. In addition, studies on bv-FTD have shown that anosognosia is correlated with hypoperfusion in the left temporal pole [1] and right frontal regions [3]. Recently, Zamboni et al [15] used FrSBe and voxel-based morphometry to show that the degree of anosognosia correlated with gray matter atrophy in a posterior region of the right superior temporal sulcus (adjacent to the temporoparietal junction).…”
Section: Discussionmentioning
confidence: 99%
“…The inability to recognize neurological symptoms has been referred to as ‘loss of insight’ [1,2] or ‘anosognosia’ [3,4], a term originally used for unawareness of illness or hemiplegia, but now adopted to denote a lack of recognition of any disease-specific acquired symptoms. Loss of insight is a core criterion for diagnosis of frontotemporal dementia (FTD) in the recent criteria for frontotemporal lobar degeneration (FTLD) [5], which is now also known to be associated with motor neuron disease.…”
Section: Introductionmentioning
confidence: 99%